Cholera vaccine clinical trials: A cross-sectional analysis of clinical trials registries - Lindi Mathebula; Thobile Malinga; Mammekwa Mokgoro; Duduzile Ndwandwe; Charles S. Wiysonge; Glenda Gray (Taylor & Francis Group, 2023)
Cholera has been one of the world's biggest public health challenges for centuries. The presence of this disease brings into focus the social determinants of health in different parts of the world. Research and development efforts to find safe and effective Cholera vaccines are critical to decreasing the disease burden from Vibrio cholerae. We searched the International Clinical Trials Registry Platform (ICTRP) and Cochrane Central Register of Controlled Trials (CENTRAL) on 5 March 2023. We included all registered randomized trials studying Cholera vaccines. We used Microsoft Excel to perform a descriptive analysis of the source registry, geographic distribution, recruitment status, phase of trials, and type of trial sponsor and presented the findings using tables and graphs. The search of ICTRP yielded 84 trials, and 315 trials were identified from CENTRAL. Seventy-four trials were included in the analysis. Most of the trials (66%, n = 49) were registered in ClinicalTrials.gov, followed by Clinical Trials Registry - India (9%, n = 7) and the Cuban Public Registry of Clinical Trials (8%, n = 6). The geographical distribution of the trials indicates that 48% (n = 36) of the trials were conducted in Asia, followed by 23% (n = 17) in North America, 15% (n = 11) in Africa, and 11% (n = 8) in Europe. Results further indicate that 81% (n = 60) of trials have a recruitment status "Not recruiting," followed by 12% (n = 9) with a status "recruiting." With the recent surge in Cholera cases and the limited supply of Cholera vaccines, research indicates the need for Cholera vaccine trials to ensure the availability of vaccines, especially in populations affected.